2021
DOI: 10.1007/s10653-021-01020-y
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and health risk assessment of potentially toxic elements in popcorn kernel from sandy loam Ferric Luvisol amended with municipal solid waste compost

Abstract: Application of municipal solid waste compost (MSWC) to marginal soil enhances crop growth but could also serve as source of pollutants into agroecosystem. There is scanty report on bioavailability of potentially toxic element (PTE) and the health risk of consuming popcorn kernel harvested from field fertilized with MSWC. Field trial was carried out in 2017–2019 to evaluate bioavailability of PTEs in kernel of popcorn harvested from field fertilized with MSWC. The trial was conducted at the experimental field o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Excess soil amendment did not increase grain yield or mineral concentrations [16]. When the amount of organic soil amendment was increased, Dada and Kutu [34] found that maize grain mineral concentrations decreased. In this study, the highest application of organic amendment under the PM amendment resulted in a similarly reduced mineral concentration in maize grain.…”
Section: The Effect Of Soil Amendments On Grain Mineral Concentrationsmentioning
confidence: 88%
“…Excess soil amendment did not increase grain yield or mineral concentrations [16]. When the amount of organic soil amendment was increased, Dada and Kutu [34] found that maize grain mineral concentrations decreased. In this study, the highest application of organic amendment under the PM amendment resulted in a similarly reduced mineral concentration in maize grain.…”
Section: The Effect Of Soil Amendments On Grain Mineral Concentrationsmentioning
confidence: 88%
“…A heap containing a mixture of the organic materials was prepared at a ratio of 5 : 4 : 2 : 3 (MSW:PM:CM:SM) on dry weight (kg) basis. The chemical composition of the sorted municipal solid waste prior to cocomposting is as reported by Dada and Kutu [ 25 ]. Thermophilic anaerobic heap method described by Kutu et al [ 26 ] was used for the decomposition process.…”
Section: Methodsmentioning
confidence: 99%
“…Anthropogenic activities in industries, mining sites, refineries, refuse dumping and burning sites as well as farming, release innumerable contaminants into the atmosphere, ground and aquatic environment, threatening both biotic and abiotic ecosystems (Huang et al, 2016). Most contaminants are not biodegradable, reaching water sources, and causing ecological and human health threats (Dada and Kutu, 2022). Human and environmental contaminants are composed of all forms of ionic species, which have agglomerated into cationic and anionic contaminants, some of which are highly essential such as; Ca 2+ , K + , Ag + , Na + , Co 2+ , Fe 2+ , Fe 3+ and Mg 2+ but harmful at excessive exposure or ingestion to humans.…”
Section: Introductionmentioning
confidence: 99%